Kidney versus combined kidney and liver transplantation in young people with autosomal recessive polycystic kidney disease: data from the European Society for Pediatric Nephrology/European Renal Association-European Dialysis and Transplant (ESPN/ERA-EDTA) Registry - Mekahli, Djalila; Schaefer, Franz (American journal of kidney diseases, 2016)
The choice for either kidney or combined liver-kidney transplantation in young people with kidney failure and liver fibrosis due to autosomal recessive polycystic kidney disease (ARPKD) can be challenging. We aimed to analyze the characteristics and outcomes of transplantation type in these children, adolescents, and young adults. Cohort study. We derived data for children, adolescents, and young adults with ARPKD with either kidney or combined liver-kidney transplants for 1995 to 2012 from the ESPN/ERA-EDTA Registry, a European pediatric renal registry collecting data from 36 European countries. Liver transplantation. Transplantation and patient survival. 202 patients with ARPKD aged 19 years or younger underwent transplantation after a median of 0.4 (IQR, 0.0-1.4) years on dialysis therapy at a median age of 9.0 (IQR, 4.1-13.7) years. 32 (15.8%) underwent combined liver-kidney transplantation, 163 (80.7%) underwent kidney transplantation, and 7 (3.5%) were excluded because transplantation type was unknown. Age- and sex-adjusted 5-year patient survival posttransplantation was 95.5% (95% CI, 92.4%-98.8%) overall: 97.4% (95% CI, 94.9%-100.0%) for patients with kidney transplantation in contrast to 87.0% (95% CI, 75.8%-99.8%) with combined liver-kidney transplantation. The age- and sex-adjusted risk for death after combined liver-kidney transplantation was 6.7-fold (95% CI, 1.8- to 25.4-fold) greater than after kidney transplantation (P=0.005). Five-year death-censored kidney transplant survival following combined liver-kidney and kidney transplantation was similar (92.1% vs 85.9%; P=0.4). No data for liver disease of kidney therapy recipients. Combined liver-kidney transplantation in ARPKD is associated with increased mortality compared to kidney transplantation in our large observational study and was not associated with improved 5-year kidney transplant survival. Long-term follow-up of both kidney and liver involvement are needed to better delineate the optimal transplantation strategy.